Características demográficas y psicosociales de los agresores sexuales (2010)
The article describes demographic and psychosocial characteristics associated with the behavior of sexual aggressors. The first characteristics described are: Marital status, number of jobs, age of the first commited crime, and the relationship with the victims. According to the socio-familiar background, some points described are: The story about failure during school years, the story about abuse in the family of origin and the sexual abuse background and the story of alcoholism in the family of origin. Significant connections were found between the abuse, the age of the first commited crime, failure in the school and the physical and sexual abuse. Connections between the number of jobs and the sexual aggression were not found, and even though the literature indicates that there are more cases were aggressors were relatives or known by the victims, in this research this particular variable was found in only 25% of the cases.